Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.aap.2013.07.029
|View full text |Cite
|
Sign up to set email alerts
|

A system of safety management practices and worker engagement for reducing and preventing accidents: An empirical and theoretical investigation

Abstract: Even though the presence of safety management system practices is linked with incident reduction and may represent a necessary first-step in accident prevention, safety performance may also depend on mediation by safety-focused cognitive and emotional engagement by workers. Thus, when organizations invest in a safety management system approach to reducing/preventing accidents and improving safety performance, they should also be concerned about winning over the minds and hearts of their workers through human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
177
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(213 citation statements)
references
References 23 publications
11
177
1
7
Order By: Relevance
“…This result is coherent with the findings of Yeh (2014). Organizational support theory and social exchange theory helped with explaining the antecedents and results of affective commitment in many studies such as Rhoades et al (2001) and Wachter and Yorio, (2014). Similarly, Huang et al (2006) state that administration with proactive and constructive return-to-work policies would likely deliver a powerful message to employees since their physical and psychological well-being is matter of importance for organization.…”
Section: Impact Of Occupational Health and Safety Practices On Organisupporting
confidence: 77%
See 1 more Smart Citation
“…This result is coherent with the findings of Yeh (2014). Organizational support theory and social exchange theory helped with explaining the antecedents and results of affective commitment in many studies such as Rhoades et al (2001) and Wachter and Yorio, (2014). Similarly, Huang et al (2006) state that administration with proactive and constructive return-to-work policies would likely deliver a powerful message to employees since their physical and psychological well-being is matter of importance for organization.…”
Section: Impact Of Occupational Health and Safety Practices On Organisupporting
confidence: 77%
“…Workplace health and safety is expected to influence organizational commitment (DeJoy et al, 2010). Wachter and Yorio (2014) suggested that when organizations invested in a safety management system they approached towards improving the performance of accident reduction/prevention and the occupational safety. Such organizations stated that they also cared for winning the hearts and minds of their workers thanks to human performance systems based on safety management in order to develop and improve organizational commitment in workers.…”
Section: Introductionmentioning
confidence: 99%
“…This creates the safety culture and the employee's engagement is related to the level of the employees' involvement in their work processes. The effectiveness of a safety management system depends on the levels of safety-focused cognitive and emotional worker's engagement [9].…”
Section: Introductionmentioning
confidence: 99%
“…Il pénètre tous les composants de l'organisation, et implique toutes les phases du cycle de vie, de la conception à la démolition (Hale et al, 1997 (Mearns et al, 2003), il est complètement intégré à l'organisation (Labodova, 2004), et peut être vu comme un système rationnel qui poursuit des objectifs spécifiques et montre une structure sociale formalisée (Wachter et al, 2013). Il reflète également l'engagement de la direction pour la sécurité.…”
Section: Sgs : Quelle(s) Définition(s) ?unclassified